Lunar Position Calculation Algorithm With Truncated ELP/MPP02 Series - Abdillah, Yusrifal Fais; Dzulikrom, Muhammad Muadz (University of Muhammadiyah Sumatera Utara, 2024)
The truncated ELP/MPP02 series is a series of lunar position calculations based on the ELP/MPP02 theory developed by Chapront and Francou in 2002. This series reduces the lunar correction data, reducing the number of corrections from 35,901 to 253 data points, which are used to calculate the ecliptic longitude, ecliptic latitude and distance of the Moon from the Earth. The conclusions of this research are as follows: First, the calculation of lunar coordinates with the truncated ELP/MPP02 series involves the calculation of ecliptic longitude (L), ecliptic latitude (B), and the distance of the Moon from Earth (R) using the provided periodic terms, and then correcting for Δλ and Δψ to calculate the apparent position of the Moon. Secondly, the truncated ELP/MPP02 series has a maximum error of 5'' for L, 1.26'' for B and 2.43 km for R in the time range 0 AD to 3000 AD. In the case of L, B and R, these errors do not exceed 5', 1' and 14 km respectively when calculations are made between 3000 BC and 1000 BC. For lunar and solar eclipses, the series shows an accuracy of 5.8 seconds for lunar eclipses in the time range 2000 AD to 2050 AD, and 4 seconds for solar eclipses.